Organizational behavior 4 - Miner, John B. (M.E. Sharpe Organizational Behavior series., 2007)
Bridging the gap between theory and practice in organizational behavior, this book provides a practical guide to real-life applications of the 35 most significant theories in the field. It covers key managerial topics such as goal setting, training and development, assessment, job enrichment, influence processes, decision-making, and others.